First Experience in Living Liver Donation From Donors With Sickle Cell Trait - Maren Schulze, MD, PhD, FACS; Ahmed Zidan, MD, PhD; Mark Sturdevant, MD; Sultan Aljudaibi, MD; Mohammad Shagrani, MD; Khalid Bzeizi, MD, FRCP; Saleh Alqahtani, MD; Dieter C. Broering, MD, PhD, FACS, FEBS (Transplantation Direct, 2022)
Background. Living donor liver transplantation is the main source of organs in the Middle East. Therefore, well balanced criteria are needed to avoid unnecessary exclusion of potential donors, while prioritizing donor safety. We face a high incidence of sickle cell trait (SCT; and disease). Therefore, there is vast experience in general and cardiac surgeries in SCT carriers at our center. After studying their management in detail, we considered accepting SCT carriers as living liver donors, on an exceptional basis. This the first single-center case series of living donor liver transplantation with SCT. Methods. Between January 2012 and September 2021, 20 donors with SCT were reviewed for age, gender, relation to the recipient, hemoglobin, hemoglobin S (HbS), surgical approach, intensive care unit stay, donor and recipients’ complications, and graft and recipient survival. Results. Average age of donors was 28.4 y. Sixteen donated the left lateral segment, 4 the left lobe. Recipients were related children or adults. HbS ranged from 21.2% to 39.9%, being ≥30% in 14 donors. HbS was reduced by phlebotomy or exchange transfusion. We performed 7 open, one laparoscopic, and 12 robotic donor surgeries. Operating room time, blood loss, and intensive care unit stay were comparable to non-SCT donors. There was no SCT-related complication. All donors are alive and free of thromboembolic events. Graft and recipient survival is 100% until follow-up. Conclusion. Our experience should encourage other countries with high incidence of SCT to report their experience with this donor population.